Observation instrument for student social attitude in primary schools: Validity and reliability - Ari Setiawan; Widowati Pusporini; Hanandyo Dardjito (Graduate School, Universitas Negeri Yogyakarta, 2020)
This study aims to (1) identify the content validity of observations of students' social attitudes, (2) identify the construct validity of the observation instruments of students 'social attitudes, and (3) identify the reliability of observations of students' social attitudes. The subjects of this study were grades IV and V of elementary school students in Yogyakarta province selected using cluster random sampling. Observation guidelines were used to collect the data using a summative rating scale model. The content validity was analyzed by applying Aiken assisted by Microsoft Excel, the construct validity by using second-order Confirmatory Factor Analysis assisted by Lisrel, and the reliability by using the Omega reliability approach. The results indicate that all items are valid by which the content validity. The construct validity with the Confirmatory Factor Analysis is high. The reliability values of the observation instruments are reliable.